ANALISIS KONSEP FISIKA SUHU DAN KALOR PADA PROSES PEMBUATAN PERMEN KAPAS (COTTON CANDY) SEBAGAI RANCANGAN LKPD - Jariyah, Ayu Ainun; Prihandono, Trapsilo; Nila Mutia Dewi (JEAS (Journal of Educational and Applied Science), 2024)
This study aims to improve student learning outcomes through the design of LKPD from the analysis of the physics concepts of temperature and heat in the process of making cotton candy. This type of research is descriptive qualitative. The stages in this research are: identification, instrument making, data analysis, and preparation of research results. Data collection was done through observation, interviews, and documentation. The data analysis technique uses the stages: unitizing, sampling, recording, reducing, inferring, and narrating. The results of this study indicate that the process of making cotton candy is one of the applications of physics concepts that fulfill the subject matter of temperature and heat. this is evidenced by the results of observations of the process of making cotton candy which is then coupled with temperature measurements and mathematical calculations of heat. so that the results of this study can be applied to LKPD which helps make it easier for students to understand the concepts of temperature and heat. The difficulty of students in understanding the concepts of temperature and heat often occurs because of the inappropriate learning approach used by the teacher. with the LKPD as an implementation of research on the analysis of the physics concepts of temperature and heat in the process of making cotton candy is expected to help make it easier for students to understand the concepts of temperature and heat.